PENGARUH MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI “INDONESIAKU KAYA BUDAYA” - Pasaribu, Elisa Febriani; Angin, Laurensia Masri Perangin; Tamba, Robenhart; Manurung, Imelda Free Unita; Siregar, Fajar Sidik (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to determine the effect of the Numbered Heads Together (NHT) learning model assisted by Wordwall media on students' learning outcomes in the topic "My Culturally Rich Indonesia" in fourth-grade students at SDN 101768 Tembung. The research was motivated by low student achievement in IPAS (Science and Social Studies Integration), limited use of varied teaching methods, and lack of interactive media. This quantitative study used a quasi-experimental method with a non-equivalent control group design. The research subjects were two fourth-grade classes, IV-A as the control group and IV-B as the experimental group, each consisting of 16 students. The research instrument was a multiple-choice test administered as a pretest and posttest. The analysis showed a significant difference in posttest scores between the experimental and control groups. The NHT model assisted by Wordwall significantly improved student learning outcomes in cognitive, affective, and psychomotor domains. Therefore, the NHT model with Wordwall is effective in enhancing student engagement and academic performance in integrated IPAS learning.